Data-driven insights into protonic-ceramic fuel cell and electrolysis performance - Meisel, C.; Huang, J.D.; Le, L.Q.; Kim, Y.D.; Stockburger, S.; Luo, Z.; Zhu, T.; Wang, Z.; Shao, Zongping; O'Hayre, R.; Sullivan, N.P. (2025)
Cell reproducibility remains a significant challenge for emerging proton-conducting ceramic electrochemical fuel cell and electrolyzer technologies. This study investigates the factors contributing to cell-to-cell performance variation. Gaussian process and random forest regressor machine learning models were utilized to analyze 86 cells for fuel cell performance and 84 cells for electrolysis performance. The study focused on BaCe0.4Zr0.4Y0.1Yb0.1O3−δ (BCZYYb4411) + NiO—BCZYYb4411—BaCo0.4Fe0.4Zr0.1Y0.1O3−δ (BCFZY) material sets for the negatrode, electrolyte, and positrode, respectively. Key processing and morphological parameters impacting performance were identified. The electrolyte thickness to grain size ratio emerged as a critical factor for both fuel cell and electrolysis performance, with maximum gains at ratios ≤1. A NiO particle size threshold of ∼6 μm was identified, below which performance increases markedly. Evaporating organics from the electrolyte spray or positrode application process before sintering may improve performance significantly, but the extent of this improvement remains uncertain. The optimal BCFZY positrode thickness for fuel cell performance is 20-25 μm. Fuel cell performance is primarily influenced by positrode microstructure. Optimizing this microstructure can bring the largest benefit to fuel-cell performance through reduced polarization resistances. In contrast, electrolysis performance is strongly governed by electrolyte microstructure. Improving electrolyte conductivity and reducing ohmic resistance greatly benefits electrolysis performance.